(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The increase in the number of video cameras causes an explosive increase in the number of cameras captured. Video, mainly, the increase in the number of millions of surveillance cameras operating throughout the day. Video Browsing and rehabilitation take time, while the video synopsis is one of the most potent rehabilitation methods. It can start browsing and indexing a video that allows hours of video in just a few minutes. Costly and costly is also how to produce a video synopsis and retain the essential activities of the original film. Job demanding and time-consuming. In this case, Paper, The new approach suggested for video synopsis to create the condensed video, which uses an object tracking method for extracting the video and its key objects and images. This technique creates video tubes, and the original film is condensed. Experiential results suggest that a high condensation rate can be reached in the preservation of all related artifacts. This method will thus allow users to access the data monitoring footage easily.